Hubungan Minat Baca dengan Kemampuan Menulis Teks Eksposisi Siswa Kelas XI SMK Negeri 9 Samarinda - Kristina Septhin; W. G. Mulawarman; Bibit Suhatmady (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2018)
This study aims to find out the relationship between reading interest and the ability to write exposition text of class XI students of SMK Negeri 9 Samarinda. This research is a quantitative research with Product Moment correlation analysis. The population in this study were class XI students of SMK Negeri 9, which amounted to 261 students. The research sample amounted to 166 students. The sampling technique used cluster random sampling. There were three variables in this study, two independent variables and one dependent variable. Questionnaires and tests were used to collect the data. Based on the analysis of the data it can be concluded it seems that there is a positive and significant relationship between reading interest in the ability to write exposition texts in class XI students of SMK Negeri 9 Samarinda which is indicated by a correlation coefficient (rx1y) of 0.305 and a calculated value greater than rtable with N = 166 at the error rate of 5% (0.305> 0.159) which means that the higher the reading interest of students, the higher the ability to write exposition text.